Entrepreneurial finance at the dawn of industry 4.0 - Quan Hoang Vuong (MDPI, 2020)
The advent of the fourth industrial revolution, Industry 4.0, brings about both opportunities and challenges that are likely to set developed economies even farther apart from emerging economies. This book, through the perspective of researchers in the emerging markets, presents analyses on a number of issues important to entrepreneurial finance, such as debt financing, mergers and acquisitions, stock market efficiency, resource allocation and consumption, and sustainable development. It aims at improving our understanding of the financing needs as well as the financial risks involved in entrepreneurial endeavors in less developed settings in the new era.
Keywords: 330; Microfinance; crow-funding; Artificial intelligence (AI) and computational entrepreneurship; Serendipity as a strategic advantage in entrepreneurial finance; Governmental policy; responses to entrepreneurs' financial needs; Finance and creative performance in Industry 4.0; Philanthropic funding; scientific discoveries; and entrepreneurial finance; Emerging regulatory framework amid the rise of Industry 4.0; The role of financial markets; Gender issues in entrepreneurial finance; Risk management for entrepreneurial finance: tools; techniques; conceptual developments and limitations